E-government.
a. This text provides selected examples of current developments from various countries in terms of technology, applications and services, and various real world m-government examples. b. Provides an understanding on contemporary experiences on technological, societal and legal setups of e-Government implementation in emerging economies. c. Covering such issues as e-government adoption and diffusion; social and performance issues of e-government; and information security, privacy, and policy, this book is an essential resource to any library collection.